KONSEP PEMBANGUNAN BERKELANJUTAN STUDI KASUS: KOTA BANDUNG DENGAN TUJUH PROGRAM PRIORITAS - Rosada, Dada (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
Sustainable development is a planned, systematic process of satisfying the needs of economic, social and environmental welfare for current and future generations without jeopardizing people in the next generation. One of the principles in sustainable development is the participation of stakeholders. Each stakeholder has resources and roles that can be utilized proportionally.Sustainable development exterminates the old paradigm that the government plays role as the provider. In this concept, the government functions as the facilitator and citizen empowering agent. Awareness on sustainable development through environmental conservation, is believed to be social phenomenon of the fourth wave of civilization after the three previous ones: agriculture, industry, and information technology. It enables the nature to regenerate so that it can safeguard and preserve the natural affluence for citizen life.